'They can pull in their head': a case of Chrysemys scripta elegans. - Santos-König U (Homoeopathic Links, 2007)
This case is an example of how the themes present in a case can point to a specific group of remedies, in this case the sea remedies, and how peculiarities in the case help to find the particular remedy within the family.